(untitled) (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
The article analyzes gastronomic tourism, particularly its wine segment, which integrates the economic, social, and cultural aspects of regional development. The experience of leading wine-producing countries—Italy, France, and Spain—alongside emerging players such as Australia, Argentina, and Chile, is examined. Key success factors for wine tourism are identified: integration of regional traditions, eco-friendly production practices, innovative technologies, development of tourist infrastructure, and the use of digital marketing tools. Wine tourism promotes brand recognition, boosts sales, and attracts tourists through the organization of tastings, guided tours, sports, and cultural activities. Special attention is paid to the role of UNESCO sites, national strategies, and a cluster-based approach in advancing the sector. The prospects for developing wine tourism in Ukraine are considered in the context of post-war recovery. The resource potential of regions such as Zakarpattia, Northern Black Sea Coast, and Odesa is analyzed. Challenges related to wartime disruptions are highlighted, but so is the adaptability of Ukrainian producers, who are introducing new formats for tourism services. Recommendations for Ukraine include developing marketing strategies that leverage digital platforms, expanding service offerings, modernizing infrastructure, implementing eco-friendly standards, and launching educational initiatives in wine tourism. Integrating wine routes with cultural and gastronomic events, along with fostering international partnerships, is crucial. The article concludes that wine tourism in Ukraine can become a driver of economic growth, enhance international competitiveness, and contribute to the promotion of Ukrainian culture and winemaking.